W sprawie projektu Preambuły do Konstytucji Unii Europejskiej - Paradowski, Ryszard (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2007)
We, the citizens of Europe, having grievously suffered from wars, despotic regimes, alliances of throne and altar, religious repressions, and genocidal totalitarian dictatorships, knowing the high price of the democratic political orders and being determined to defend them from authoritarian movements and organizations, declaring our connection to the democratic European tradition and democratic values, such as the natural right of every human being to participate in public debate and to codefine the public good, to constitute, control and recall the political representatives of every level and to define their competence, and other democratic values contained in the great constitutions, such as Magna Carta, The Declaration of The Rights of Man and Citizen, T he General Declaration of Human Rights, The European Convention of The Protection of Human Rights and Fundamental Freedom, The European Social Cart.
About the proposal of the Introduction to the Constitution of the European Union